2020
DOI: 10.1136/bmjsem-2019-000645
|View full text |Cite
|
Sign up to set email alerts
|

Lay of the land: narrative synthesis of tackle research in rugby union and rugby sevens

Abstract: ObjectivesThe purpose of this review was to synthesise both injury prevention and performance tackle-related research to provide rugby stakeholders with information on tackle injury epidemiology, including tackle injury risk factors and performance determinants, and to discuss potential preventative measures.DesignSystematic review and narrative synthesis.Data sourcesPubMed, Scopus and Web of Science.Eligibility criteriaLimited to peer-reviewed English-only publications between January 1995 and October 2018.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 167 publications
1
27
0
1
Order By: Relevance
“…It may be that international players find themselves in contact situations more regularly or they have a higher propensity for risk-taking behaviour, both of which may make them better players and, therefore, more likely to be selected at international level. The conclusions are supported in a recent review by Burger et al who found that concussive injuries are most likely to occur in rugby players playing at a higher level of competition 42…”
Section: Discussionsupporting
confidence: 63%
“…It may be that international players find themselves in contact situations more regularly or they have a higher propensity for risk-taking behaviour, both of which may make them better players and, therefore, more likely to be selected at international level. The conclusions are supported in a recent review by Burger et al who found that concussive injuries are most likely to occur in rugby players playing at a higher level of competition 42…”
Section: Discussionsupporting
confidence: 63%
“…37 The risk of tackle injury is nearly doubled in professional players relative to players from lower tiers of the game. 38 FF forwards are the most likely to be substituted (often after about an hour of a match) and are those who have the greatest momentum along with the BR. Notwithstanding the legal action being prosecuted by a group of former players diagnosed with dementia linked to repeated head injuries and early retirements due to injury, World Rugby has made rule changes (around tackle height) to reduce the number of concussive and subconcussive injuries sustained.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it was noted that these injuries, typically the most severe, occur relatively more frequently towards the end of the match attributed to fatigue affecting tackle technique. 38 While it is feasible that better player conditioning for contact could mitigate some of the effects of increased momentum on injuries, the current substitution laws enable mismatches which may increase the risk of mistimed or misplaced collisions, especially later in the game. An open letter from the Progressive Rugby organisation has directly called substitutions to be used for injury only ( https://progressiverugby.org/ ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the risks of virus transmission events during off-field behaviours (conversations and socialising), should remain a priority for community team sports who are returning. [24]…”
Section: Discussionmentioning
confidence: 99%